Surface Subsidence Prediction Method for Coal Mines with Ultrathick and Hard Stratum - Hongkai Han; Jialin Xu; Xiaozhen Wang; Jianlin Xie; Yantuan Xing (Advances in Civil Engineering)
Overburden conditions consisting of ultrathick and hard stratum (UTHS) are widespread in China and other countries, but existing surface subsidence prediction methods ignore the strong impact of UTHS on surface subsidence. They are thus not applicable for surface subsidence prediction for coal mining with the presence of UTHS. We conducted actual measurements of surface and UTHS subsidence in the Tingnan Coal Mine. The results showed that under the UTHS mining condition, the required gob dimension is much larger than the empirical value when the surface reaches sufficient mining and that the actual measured maximum value of surface subsidence is much smaller than the empirical value. The UTHS subsidence is approximately equal to the surface subsidence. The movement of UTHS has a strong impact on surface subsidence and has a controlling function for it. It was proposed that surface subsidence could be approximately predicted by calculating the UTHS subsidence. The UTHS movement characteristics were studied using Winkler’s theory of beams on an elastic foundation, the subsidence prediction equation of the main sections in the strike and dip directions was obtained under different mining dimensions, and the subsidence prediction equation of any arbitrary cross section parallel to the two main sections was established. Then, the surface subsidence prediction method for coal mining with the presence of UTHS was developed, and the influences of UTHS thickness, strength, and layer position on the surface subsidence were discussed. The Tingnan Coal Mine was taken as an example, and the subsidence curves of the strike and dip main sections were calculated using different mining dimensions. Subsequently, the surface subsidence after the mining of working faces 204, 205, 206, and 207, respectively, was predicted, and the prediction method was verified by comparing the results with the measured surface subsidence results of working faces 204, 205, and 206.